Microtubule flux in mitosis is independent of chromosomes, centrosomes, and antiparallel microtubules. - Sawin, K E (1994)
We investigated the mechanism of poleward microtubule flux in the mitotic spindle by generating spindle subassemblies in Xenopus egg extracts in vitro and assaying their ability to flux by photoactivation of fluorescence and low-light multichannel fluorescence video-microscopy. We find that monopolar intermediates of in vitro spindle assembly (half-spindles) exhibit normal poleward flux, as do astral microtubule arrays induced by the addition of dimethyl sulfoxide to egg extracts in the absence of both chromosomes and conventional centrosomes. Immunodepletion of the kinesin-related microtubule motor protein Eg5, a candidate flux motor, suggests that Eg5 is not required for flux. These results suggest that poleward flux is a basic element of microtubule behavior exhibited by even simple self-organized microtubule arrays and presumably underlies the most elementary levels of spindle morphogenesis.